Characterization of Mutations in the rpoB Gene Associated with Rifampin Resistance in Rhodococcus equi Isolated from Foals - Fines, Marguerite (American Society for Microbiology, 2001)
Treatment with a combination of erythromycin and rifampin has considerably improved survival rates of foals and immunocompromised patients suffering from severe pneumonia caused by Rhodococcus equi. Frequently, because of monotherapy, emergence of rifampin-resistant strains has been responsible for treatment failure. Using consensus oligonucleotides, we have amplified and sequenced the rifampin resistance (Rif(r))-determining regions of 12 rifampin-resistant R. equi strains isolated from three foals and of mutants selected in vitro from R. equi ATCC 3701, a rifampin-susceptible strain. The deduced amino acid sequences compared to those of four rifampin-susceptible R. equi strains showed several types of mutations. In 3 of the 10 strains isolated from one foal, His526Asn (Escherichia coli numbering) and Asp516Val mutations were associated with low-level resistance (rifampin MIC, 2 to 8 μg/ml), whereas His526Asp conferred high-level resistance (rifampin MIC, 128 μg/ml) in the 7 remaining strains. In strains from the two other foals, His526Asp and Ser531Leu mutations were found to be associated with high-level and low-level resistance, respectively. The in vitro mutants, highly resistant to rifampin, harbored His526Tyr and His526Arg substitutions. As described in other bacterial genera, His526, Ser531, and Asp516 are critical residues for rifampin resistance in R. equi, and the resistance levels are dependent on both the location and the nature of the substitution.